Evaluation of Teacher Practices on Competency-Based Assessment Methods in Lower Primary Grades in Siaya County, Kenya - Ombese Sollome Nyaboke; Benson Charles Odongo; Cleophas Owino Owiko (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: The Competency-Based Assessment Framework for Early Years Education (CBA-F-EYE) recommends that teachers employ a variety of methods and tools to gather evidence of learner performance, document this evidence, and provide feedback to inform instructional decisions and policy interventions. Aims and scope of paper: Guided by this perspective, the current study examined teacher practices in the use of Competency-Based Assessment (CBA) methods in lower primary grades within public schools in Siaya County. The study was philosophically grounded in constructivism and employed a qualitative approach using a phenomenological research design. The theoretical framework was informed by Lev Vygotsky’s social constructivism theory (1896–1934). Methods: The target population included 1,968 lower primary teachers, 656 head teachers, and one County Quality Assurance and Standards Officer (CQASO). A purposive sample of 24 teachers, 12 head teachers, and one CQASO was selected. Data collection methods included in-depth interviews, observation protocols, and document analysis guides. Instrument reliability was ensured through a pilot study, while authenticity, credibility, and trustworthiness were reinforced through triangulation of data sources. Thematic analysis was used to interpret the data. Results: The findings revealed three major themes: inadequate understanding of CBA concepts among teachers, non-compliance with prescribed CBA assessment methods, and an unsupportive implementation environment characterized by inadequate training, large class sizes, heavy workloads, and insufficient instructional resources. Most teachers predominantly relied on oral questioning and written exercises, while authentic assessment approaches such as rubrics, portfolios, projects, and observation schedules were minimally utilized. The study further found that many teachers conceptualized assessment as a process of testing knowledge acquisition rather than evaluating learners’ competencies, skills, values, and practical application of learning. Contribution: The study has developed a framework that school administrators can use as comprehensive mechanisms for classroom-based assessment that balance formative and summative approaches, thereby capturing learners’ knowledge, skills, and values more effectively.